2022
DOI: 10.1101/2022.03.30.486448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age at cancer diagnosis by breed, weight, sex, and cancer type in a cohort of over 3,000 dogs: determining the optimal age to initiate cancer screening in canine patients

Abstract: The goal of cancer screening is to detect disease at an early stage when treatment may be more effective. Until recently, cancer screening in dogs has relied upon annual physical examinations and routine laboratory tests, which are largely inadequate for detecting preclinical disease. With the introduction of non-invasive liquid biopsy cancer detection methods, the discussion is shifting from How to screen dogs for cancer to When to screen dogs for cancer. To address this question, data from 3,452 cancer-diagn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Cancer screening using NGS-based liquid biopsy may offer an of cancer, liquid biopsy was able to detect disease in nearly 50% of patients. Therefore, the addition of liquid biopsy to a dog's annual or semi-annual wellness visit (starting at age 7 for all dogs, or earlier for certain breeds 13 ) may enhance both preclinical and early-stage cancer detection in dogs and may expand the breadth of cancer types that may be detectable during routine care or at a wellness visit.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer screening using NGS-based liquid biopsy may offer an of cancer, liquid biopsy was able to detect disease in nearly 50% of patients. Therefore, the addition of liquid biopsy to a dog's annual or semi-annual wellness visit (starting at age 7 for all dogs, or earlier for certain breeds 13 ) may enhance both preclinical and early-stage cancer detection in dogs and may expand the breadth of cancer types that may be detectable during routine care or at a wellness visit.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymphomas were more frequently seen in male cats than female cats in another study (Dorn et al, 1968) but further research found that lymphomas had no significant correlation with sex (Shida et al, 2010). In addition, one study found that the median age of tumor incidence for cats was 9.5 years old (Pérez-Enriquez et al, 2020), while another reported a median of 9.14 years old (Rafalko et al, 2022;Pinello et al, 2022b). Further research found that tumors were most often detected between 6 and 14 years of age in cats (Pamukçu, 1954;MacEwen, 1990;Gülçubuk et al, 2005;Aydın et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Tumors are frequently observed in 6-to 14-year-old cats, with a median age of 9.1-9.5 years old (Pamukçu, 1954;MacEwen, 1990;Gülçubuk et al, 2005;Aydın et al, 2008;Rafalko et al, 2022;Pinello et al, 2022b); malignant neoplasms form a greater proportion of tumors than benign neoplasms in cats, according to Pinello et al (2022a). Moreover, Gülçubuk et al (2005) found malignant and benign tumors in 12 (36.36%) male cats between 6 and 10 years old and 24 (88.88%) female cats.…”
Section: The Correlation Between Tumor Incidence and Cat Breeds Ismentioning
confidence: 99%